Tips and Tricks to Improve Ergonomics, Efficacy, Versatility, and Overcome Limitations of Micro Percutaneous Nephrolithotomy - Biligere, Sarvajit; Heng, Chin-Tiong; Cracco, Cecilia; Mangat, Reshma; Ong, Chloe Shu-Hui; Thandapani, Karthik; Inoue, Takaaki; Sarica, Kemal; Sabnis, Ravindra B.; Desai, Mahesh; Scoffone, Cesare; Gauhar, Vineet (Frontiers in Surgery, 2021)
Percutaneous Nephrolithotomy (PCNL) has evolved over the decades from Standard to Mini to Ultramini PCNL to Micro-perc, with miniaturisation being the dominant theme and supine approach gaining momentum world over. Aim: In literature, miniaturised PCNL with microperc needle access system has raised concerns of intrarenal pressure and has some limitations with its success for larger stones. Our tips and tricks explain how to overcome these pitfalls by utilising the full construct of the needle system to its maximum potential. These will in turn help make the procedure versatile, precise, ergonomical, and enhance a surgeon's experience with improved outcomes for patients especially in large renal stones. Materials and Methods: We describe the limitations of microperc needle access as stated in literature and proposals by the co-authors using microperc for miniaturised access on how to overcome the same. Results: A simplified table describing the limitations and tips and tricks on overcoming these is provided for quick reference. Conclusion: As Technological advancements and techniques for miniaturised access in urolithiasis improve, we believe our suggestions will help surgeons overcome the quoted limitations of microperc needle access for miniaturised PCNL, making this a versatile, safe and efficacious technique even in large and complex stones. A multi centre trial will be the best way to validate the suggestions proposed in this article.